From Darwin to Hitler - Weikart, R. author. aut Link
XI, 312 p.
Keywords: In this work, Richard Weikart explains the revolutionary impact Darwinism had on ethics and morality. He demonstrates that many leading Darwinian biologists and social thinkers in Germany believed that Darwinism overturned traditional Judeo-Christian and Enlightenment ethics, especially the view that human life is sacred. Many of these thinkers supported moral relativism, yet simultaneously exalted evolutionary 'fitness' (especially intelligence and health) to the highest arbiter of morality. Darwinism played a key role in the rise not only of eugenics, but also euthanasia, infanticide, abortion and racial extermination. This was especially important in Germany, since Hitler built his view of ethics on Darwinian principles, not on nihilism.